Vanguard Alutiiq heritage practice and the import of expertise - Mason, Arthur (Études/Inuit/Studies, 2008)
AbstractThis article explores ways that Exxon Valdez oil spill restoration as well as Alutiiq identity and heritage work become articulated through a reliance on the advice of university-trained experts. The kinds of knowledge and calculation through which identity, heritage and restoration become administrable suggests that the very technologies of Alaska Native identity and heritage making are shifting. They are now increasingly linked to the larger American political landscape, capitalism, scientific authority and state intervention, as well as to local sentimentality and preservation of authority. Indigenous identity and heritage work are negotiated, contingent, open and provocative, but there are specific conditionalities.